Production sustainability and economic viability of different cropping systems under various levels of irrigation - SINGH, VED (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1993-98 on sandy-loam soil to find out the production sustainability and economic viability under various levels of irrigation on 5 cropping systems, viz upland cotton (Gossypium hirsutum L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.), desi cotton (Gossypium arboreum L.)-whcat, desi cotton-Indian mustard [Brassica .junceo (L.) Czernj. & Casson], desi cotton-sugarbeet (Beta vulgaris L.) and groundnut (Arachis hypogaea L.)-wheat. The highest seed-cotton yield of 2.18 tonnes/ha was obtained iiÂ·om desi callan with 4 irrigations in desi cotton-sugarbeet and the highest wheat grain yield of 4.45 tonnes/ha with 5 irrigations in groundnut-wheat cropping system. Desi cotton-sugarbeet cropping system gave the highest wheat-equivalent yield ( 12.4 7 tonnes/ha) and monetary net return (Rs 37 248/halyear) with 11 irrigations. followed by upland cotton-wheat (12.22 tonnes/ha/year and Rs 35 424/ha/year) with same number of irrigations. However, per irrigation highest wheat-equivalent yield (1.63 tonnes/halyear) and net return (Rs 3 916/ha/year) were recorded under desi cotton-Indian mustard, followed by desi cotton-Sligar beet and upland cotton-wheat. The mean values of wheat-equivalent yield (11.13 and 10.90 tonnes/ha/year) and net return (Rs 31 051 and Rs 29 426/ha/year) recorded respectively under desi cotton-sugarbcet and upland cotton-wheat were at par and significantly superior to all other cropping systems. However. the highest mean benefit: cost ratio of 1,97 was recorded under groundnut-wheat followed by upland cotton-wheat (1.74). The highest mean sustainability yield and value indices of 0.77 and 0.84 were recorded under groundnut-wheat. followed by desi cotton-sugarbeet (0.65 and 0.49) and desi cotton-Indian mustard (0.57 and 0.48). The highest consumptive water use (941 mm) and land-utilization effieiency (92.05%) were recorded with desi cotton-sugarbeet. followed by upland cotton-wheat (912 mID and 86.85%). Maximum water-lise efficiency (13.91 kg/ha-mm) and production efficiency (34.40 kg/ha/day) were recorded in upland cotton-wheat. followed by desi cotton-sugarbeet (13.39 kg/ha-mm and 33.12 kg/ha/day).